2001
DOI: 10.1039/b101383l
|View full text |Cite
|
Sign up to set email alerts
|

Generation and conversions of aromatic amine radical cations in acid zeolites

Abstract: Incorporation of aromatic amines, including diphenylamine (DPA), carbazole (Cbz), diphenylbenzidine (DPB) and benzidine (Bzd), into acid zeolites generated the corresponding radical cations, and DPA~`, Cbz~`, DPB~à s indicated by comparison of the characteristic long-wavelength di †use reÑectance spectra with spectra Bzd~`, observed in solution. Samples of sequestered in HZSM-5 are deprotonated ; the resulting DPA~d iphenylaminyl radical, is remarkably stable ; di †use reÑectance or EPR spectra show that a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…It has been reported that the protonated aromatic amines can be easily oxidized to form radical cations. In our case, ii‐b was oxidized to form iii. The substituted phosphate (ii‐a) then deprotonated the radical cation (iii) by the abstraction of one proton from the methyl group on iii to form the 4E free radical (iv).…”
Section: Resultsmentioning
confidence: 64%
“…It has been reported that the protonated aromatic amines can be easily oxidized to form radical cations. In our case, ii‐b was oxidized to form iii. The substituted phosphate (ii‐a) then deprotonated the radical cation (iii) by the abstraction of one proton from the methyl group on iii to form the 4E free radical (iv).…”
Section: Resultsmentioning
confidence: 64%
“…1,2 One of the most interesting properties of acid zeolites is their ability to spontaneously generate organic radical cations upon adsorption of electron donor molecules. [3][4][5] These species can also be generated by ␥ radiation of zeolites containing organic molecules. 3,6,7 The ␥ radiation generates a free electron and a hole in the zeolite in such a way that an electron transfer from the guest to the zeolite can occur leading to the desired radical cation.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] These species can also be generated by ␥ radiation of zeolites containing organic molecules. 3,6,7 The ␥ radiation generates a free electron and a hole in the zeolite in such a way that an electron transfer from the guest to the zeolite can occur leading to the desired radical cation. This process is suggested to occur when the ionization energy of the guest molecule is lower than 10.0-10.5 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilized radical cations CBZ •+ were also detected in low temperature polymer matrices 31 and in zeolites. 32 The position of the maximum and the widths of spectral bands are strongly dependent on the environment. Localization of the excess electron in acetonitrile has been an intensively debatable issue (see Ref.…”
Section: Resultsmentioning
confidence: 99%